Effects of Physical Exercise on Executive Functions of Individuals with Schizophrenia Spectrum Disorders: Protocol for a Systematic Review and Meta-Analysis - Arellano-Roco, C (Public Library of Science, 2024)
Introduction Executive functions are commonly impaired in individuals with schizophrenia spectrum disorders. Physical exercise has the potential for improving executive functions and can be easily implemented as a therapeutic method. However, there are only few systematic reviews of exercise effects in schizophrenia including cognitive outcomes, and no meta-analytical syntheses of effects on “cool” and “hot” executive functions. The purpose of this systematic review and meta-analysis will be to determine the effects of physical exercise on “cool” and “hot” executive functions of adults with schizophrenia spectrum disorders. Methods and analysis This protocol was guided by PRISMA-P guidelines. Studies will be searched using combinations of keywords and medical terms in the Web of Science, PubMed, Scopus, and EBSCO databases. Inclusion criteria will be determined as per PICOS approach. The risk of bias will be assessed using the Cochrane RoB2 tool. The certainty of evidence (per outcome) will be assessed using the GRADE method. The meta-analyses will be performed using the DerSimonian and Laird random effects model. Effect sizes (Hedges’ g) with 95% confidence intervals will be calculated for each main outcome. Conclusions The results of this review may be useful for mental health professionals to design treatment plans for adults with schizophrenia spectrum disorders, offering potential benefits related to the quality of life and cognitive abilities of this population. © 2024 Public Library of Science. All rights reserved.